Production of fresh fish sausages containing natural preservatives (Laurus nobilis L.) it's nutritional composition and oxidative stability - Coban, Ozlem Emir (Mattioli 1885, 2020)
Aim: The aim of this study was develop the fresh fish sausage containing natural protective from rainbow trout (Oncorhynchus mykiss) and it's was investigate the nutritional composition and oxidative stability during storage at 2 degrees C. Method: For this purpose were stored the fresh trout sausages added 2% Laurus nobilis extract and 4% Laurus nobilis extract for 10 days. Three different sausage formulations were analyzed for nutritional composition and lipid oxidation products (total volatile base nitrogen (TVB-N) thiobarbituric acid (TBA), peroxide value (PV) and free fatty acids (FFAs)). Results: The formulated fresh trout sausages determined 68.11-68.26% moisture, 18.06-18.25% protein, 6.12-6.15% lipid, 3.14-4.28% ash as good quality and might buy. According to oxidative stability results the highest levels of TVB-N TBARS, PV and FFAs were related to the control group and the least amount of these parameters was determined in Lauris nobilis extract (LE) applications. Conclusion: Based on the this datas, it can be deduced that the LE successfully improve the oxidative stability of the fresh trout sausages in the cold storage
Keywords: Oncorhynchus mykiss; Fresh fish sausage; Laurus nobilis; Natural preservative; Lipid oxidation